Circadian disruption dysregulates lung gene expression associated with inflammatory lung injury - Casanova, Nancy G.; De Armond, Richard L.; Sammani, Saad; Sun, Xiaoguang; Sun, Belinda; Kempf, Carrie; Bime, Christian; Garcia, Joe G. N.; Parthasarathy, Sairam (Frontiers in Immunology, 2024)
Rationale: Circadian systems drive the expression of multiple genes in nearly all cells and coordinate cellular, tissue, and system-level processes that are critical to innate immunity regulation.We examined the effects of circadian rhythm disorganization, produced by light shifting exposure, on innate immunity-mediated inflammatory lung responses including vascular permeability and gene expression in a C57BL/6J murine model of inflammatory lung injury.Methods: 32 C57BL/6J mice were assigned to circadian phase shifting (CPS) with intratracheal phosphate buffered saline (PBS), CPS with intratracheallipopolysaccharide (LPS), control (normal lighting) condition with intratracheal PBS, and control condition with intratracheal-LPS. Bronchoalveolar lavage (BAL) protein, cell counts, tissue immunostaining and differentially expressed genes (DEGs) were measured in lung tissues at 2 weeks and 10 weeks.In mice exposed to both CPS and intratracheal-LPS, both BAL protein and cell count were increased at both 2 and 10 weeks compared to mice exposed to LPS alone. Multiple DEGs were identified in CPS-LPS-exposed lung tissues compared to LPS alone and were involved in transcriptional pathways associated with circadian rhythm disruption, regulation of lung permeability, inflammation with Rap1 signaling and regulation of actin cytoskeleton. The most dysregulated pathways included myosin light chain kinase, MAP kinase, profilin 2, fibroblast growth factor receptor, Integrin b4, and p21-associated kinase.Circadian rhythm disruption results in exacerbated immune response and dysregulated expression of cytoskeletal genes involved in regulation of epithelial and vascular barrier integrity --the mechanistic underpinnings of acute lung injury. Further studies need to explore circadian disorganization as a druggable target.